From Scrolling to Reading: Overcoming Low Motivation in English Reading Among Gen Z - Suparman, Novri; Wahyuningsih, Destri; Roswati, Roswati; Padli, Padli (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
Reading motivation among Generation Z students, particularly in English as a Foreign Language (EFL) contexts, has become a significant concern in secondary education. This study aims to investigate the factors contributing to low motivation in reading English texts among high school students in Kabupaten Indragiri Hulu and explore effective strategies to enhance their engagement. A mixed-methods approach was employed, combining surveys, interviews, and classroom observations with 150 students and 10 English teachers from SMA, SMK, and MA schools. The findings indicate that students' low reading motivation stems from digital distractions, lack of relevant reading materials, vocabulary difficulties, and insufficient external support from teachers and parents. The study also highlights that integrating digital reading platforms, gamification, personalized content, and teacher-student interactions can significantly improve reading engagement. The results align with previous research, emphasizing the importance of adapting instructional strategies to students' learning preferences. This study provides valuable insights for educators and policymakers in designing effective interventions to foster reading motivation.